An Efficient Design of QCA Full-Adder-Subtractor with Low Power Dissipation. (8th January 2021) - Gassoumi, Ismail; Touil, Lamjed; Mtibaa, Abdellatif
Abstract : The continuous market demands for high performance and energy-efficient computing systems have steered the computational paradigm and technologies towards nanoscale quantum-dot cellular automata (QCA). In this paper, novel energy- and area-efficient QCA-based adder/subtractor designs have been proposed. First, a QCA-based 3-input XOR gate is designed and then a full adder and a full subtractor are realized. The power consumption of the proposed design was tested via the QCAPro estimator tool with different kind of energy ( γ = 0.5 Ek, γ = 1.0 Ek, and γ = 1.5 Ek ) at temperature T = 2 in Kelvin. QCADesigner 2.0.03 software was applied to evaluate the simulation results of the proposed designs. The proposed design has better complexity than the conventional designs in terms of cell count, area, and power dissipation.